2021
DOI: 10.4193/rhin20.642
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary function and sinonasal mucosal cytology in pediatric patients with chronic rhinosinusitis during a year after functional endoscopic sinus surgery

Abstract: Background: The objective of the study is evaluation of ciliary function and mucosal cytology after endoscopic sinus surgery in children with chronic rhinosinusitis (CRS). Methodology: A total of 132 children with CRS who underwent endoscopic sinus surgery, as well as 15 healthy controls were involved in the study. In this follow-up study patients were examined preoperatively, as well as 3, 6, 9, and 12 months after endoscopic sinus surgery. Assessment of ciliary function and sinonasal mucosal cytology was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
0
0
2
Order By: Relevance
“…При этом в раннем послеоперационном периоде может отмечаться не только отсутствие положительной динамики, но и угнетение цилиарной активности, что обусловлено воспалительной реакцией. Устойчивое улучшение наблюдается с 6-9 месяцев и достигает нормальных показателей лишь через год после оперативного вмешательства [18]. Учитывая роль нарушений мукоцилиарного клиренса в патогенезе ХРС [2], нарушения функционирования цилиарного аппарата в послеоперационном периоде могут рассматриваться в качестве фактора риска рецидива ХРС.…”
Section: Discussionunclassified
“…При этом в раннем послеоперационном периоде может отмечаться не только отсутствие положительной динамики, но и угнетение цилиарной активности, что обусловлено воспалительной реакцией. Устойчивое улучшение наблюдается с 6-9 месяцев и достигает нормальных показателей лишь через год после оперативного вмешательства [18]. Учитывая роль нарушений мукоцилиарного клиренса в патогенезе ХРС [2], нарушения функционирования цилиарного аппарата в послеоперационном периоде могут рассматриваться в качестве фактора риска рецидива ХРС.…”
Section: Discussionunclassified
“…В частности, показано, что выраженность дисфункции цилиарного аппарата связана как с тяжестью клинического течения ХРС [4], так и эффективностью его лечения [5]. В ходе ранее проведенных нами исследований продемонстрировано, что, несмотря на значительное улучшение общего состояния после проведения ФЭРСХ, восстановление функционирования цилиарного аппарата у детей занимает длительный период вплоть до года [6]. При этом нарушение МЦТ наряду с персистированием воспаления может рассматриваться в качестве фактора снижения эффективности ФЭРСХ.…”
Section: The Impact Of Allergic Rhinitis On Ciliary Function Of Nasal...unclassified
“…A prospective observational study of 39 children affected by CRSwNP (mean age 10.9 years) undergoing ESS demonstrated an improvement in quality of life after surgery [69]. Likewise, another non-randomized controlled prospective study showed that SNOT-22, Lund-Mackay, and Lund-Kennedy scores improved after ESS in 132 children with pediatric CRS compared to 15 healthy controls [70].…”
mentioning
confidence: 98%